2023
DOI: 10.1007/s00508-023-02229-w
|View full text |Cite
|
Sign up to set email alerts
|

Austrian consensus on the diagnosis and management of portal hypertension in advanced chronic liver disease (Billroth IV)

Abstract: SummaryThe Billroth IV consensus was developed during a consensus meeting of the Austrian Society of Gastroenterology and Hepatology (ÖGGH) and the Austrian Society of Interventional Radiology (ÖGIR) held on the 26th of November 2022 in Vienna.Based on international recommendations and considering recent landmark studies, the Billroth IV consensus provides guidance regarding the diagnosis and management of portal hypertension in advanced chronic liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 238 publications
(566 reference statements)
0
7
0
Order By: Relevance
“…The present human data does not exclude that bilirubin (and possibly additional cholephiles released from the liver) may be relevant, considering that patients were selected based on a cut-off of >6 mg bilirubin/dl. The latter was chosen as it denotes liver dysfunction in the context of decompensated cirrhosis 4 and an analysis of 1,372 patients included in the above-mentioned registry study found that profound elevations of BA are uncommon in patients with lower bilirubin values (data not shown). Notably, mean arterial pressure (as a marker of circulatory dysfunction) was not included in our models, as all bar two patients with mean arterial pressures of 64 mmHg had pressures ≥65 mmHg and C-reactive protein (as a marker of systemic inflammation) was less closely associated with proximal TEC injury than sum BA concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present human data does not exclude that bilirubin (and possibly additional cholephiles released from the liver) may be relevant, considering that patients were selected based on a cut-off of >6 mg bilirubin/dl. The latter was chosen as it denotes liver dysfunction in the context of decompensated cirrhosis 4 and an analysis of 1,372 patients included in the above-mentioned registry study found that profound elevations of BA are uncommon in patients with lower bilirubin values (data not shown). Notably, mean arterial pressure (as a marker of circulatory dysfunction) was not included in our models, as all bar two patients with mean arterial pressures of 64 mmHg had pressures ≥65 mmHg and C-reactive protein (as a marker of systemic inflammation) was less closely associated with proximal TEC injury than sum BA concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury (AKI) is a frequent complication in patients with liver disease that leads to high morbidity and mortality 1 , 2 and has several causes, particularly hemodynamic changes, and infections. 1 , 3 However, an underestimated and increasingly acknowledged 4 , 5 cause of AKI in liver diseases is cholemic nephropathy (CN), 2 , 6 , 7 which describes renal dysfunction together with characteristic renal histological features such as tubular cell injury and Hall’s stain-positive bilirubin casts. It has long been known that the risk of AKI is increased in jaundiced patients.…”
Section: Introductionmentioning
confidence: 99%
“…Open access technology, and the expanding list of indications. [15][16][17][18][19][20][21] However, there remains an absence of up-to-date Australian guidance on TIPS referral pathways and practice guidelines. As a result, it is unclear whether current practices across institutions are in line with international standards.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%
“…Over recent years, clinical practice guidelines have increasingly recognised advances related to procedural techniques, TIPS stent technology, and the expanding list of indications 15–21. However, there remains an absence of up-to-date Australian guidance on TIPS referral pathways and practice guidelines.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 In early asymptomatic stages, ACLD is considered compensated. With the development of portal hypertension (PH)-related complications, including ascites, hepatic encephalopathy (HE), and variceal bleeding, patients progress to decompensated ACLD (dACLD), [3] , [4] , [5] which is associated with a considerably worse prognosis. 6 , 7 Acute-on-chronic liver failure (ACLF), defined by hepatic and/or extrahepatic organ failure(s), 8 , 9 may occur in patients with dACLD 6 , 10 and is closely associated with systemic inflammation.…”
Section: Introductionmentioning
confidence: 99%